2011
DOI: 10.1007/s10683-011-9295-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-interest and fairness: self-serving choices of justice principles

Abstract: We introduce non-enforceable property rights over a bargaining surplus in a dictator game with production, where the agent's effort is differentially rewarded and subsequently determines the size of the surplus. Using experimental data, we elicit individual preferences over the egalitarian, accountability and libertarian principles and provide evidence to support the inability of these justice principles to individually account for the observed behavior. We show that the justice principle that can be used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 34 publications
6
43
1
Order By: Relevance
“…The range of equity norms in these studies is lower, however, than in our experiment, as these results were derived mostly from behavioral data and not from observational data as in our study. Moreover, the differences in aspiration levels among strong and weak groups fits evidence from previous research on the self-serving use of fairness and social norms (e.g., [21,24,38,73,74]). …”
Section: Discussionsupporting
confidence: 82%
“…The range of equity norms in these studies is lower, however, than in our experiment, as these results were derived mostly from behavioral data and not from observational data as in our study. Moreover, the differences in aspiration levels among strong and weak groups fits evidence from previous research on the self-serving use of fairness and social norms (e.g., [21,24,38,73,74]). …”
Section: Discussionsupporting
confidence: 82%
“…Our study contributes to the literature on what people view as a fair distribution and how fairness considerations shape individual behavior (e.g., Fehr and Schmidt, 1999;Konow, 2000;Cherry, Frykblom, and Shogren, 2002;Falk, Fehr, and Fischbacher, 2003;Tyran and Sausgruber, 2006;Cappelen, Drange Hole, Sørensen, and Tungodden, 2007;Konow, Saijo, and Akai, 2009;Almås, Cappelen, Sørensen, and Tungodden, 2010;Cabrales, Miniaci, Piovesan, and Ponti, 2010;Rodriguez-Lara and Moreno-Garrido, 2012;Cappelen, Moene, Sørensen, and Tungodden, 2013b;Durante, Putterman, and Weele, 2014;Bartling, Weber, and Yao, 2015;Jakiela, 2015). A number of papers both in social psychology and in behavioral economics have shown that a majority of people appear to view income inequalities as fair if the inequalities are proportional to differences in performance (e.g., Adams, 1965;Walster, Berscheid, and Walster, 1973;Leventhal, 1980;Konow, 2000;Frohlich, Oppenheimer, and Kurki, 2004;Cappelen, Sørensen, and Tungodden, 2010;Cappelen et al, 2007Cappelen et al, , 2013a.…”
Section: Introductionmentioning
confidence: 74%
“…The results in Cherry, Frykblom and Shogren (2002) align with the theoretical prediction for selfish dictators that has favored the use of the production stage to elicit fairness attitudes toward redistribution. Some recent studies in this area are by Frohlich, Oppenheimer and Kurki (2004), Cappelen et al (2007), Oxoby and Spraggon (2008) or Rodriguez-Lara and Moreno-Garrido (2012), which argue for the importance of the earned surplus to explain subjects' preferences for fairness, although none of these studies investigate the existence of gender differences in allocation choices. As a result, we lack experimental evidence for how gender interacts with self-interest when dictators have to choose a division of the generated surplus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent findings in the experimental literature, however, suggest that individuals in a distributional problem such as the dictator game might apply principles of fairness in a self-interested manner (Rutström and Williams 2000;Rodriguez-Lara and Moreno-Garrido 2012). Further experimental evidence suggests that the underlying motivation for much fair behavior might be self-interest, albeit coupled with a desire to maintain the illusion of not being selfish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation